Nova era da cooperação: o New Development Bank e a transformação do sistema econômico-financeiro internacional - Santos, Júlia Medeiros (2024)
Based on the thoughts of Accioly (2019, p.69), it is possible to conclude that the New Development Bank (NDB) was established as a novel instrument of international financing to address the significant investment gaps in infrastructure and sustainable development projects. It serves as a crucial player in the establishment of a joint financial architecture for BRICS, with the objective of transforming the traditional economic and financial system. The monopoly held by Bretton Woods institutions over global economic governance has perpetuated a problematic development structure, deeply rooted in colonial practices that have subjected other states to conditions they were ill-equipped to implement. In this context, there has been a manifestation of these subjugated states advocating for their rightful integration and representation in the decision-making processes of multilateral actors, such as the Bandung Conference, the G20 Summit, and BRICS itself. This study aims to analyze these claims from the perspective of BRICS, specifically focusing on the capacity of the NDB to facilitate horizontal South-South cooperation, thereby promoting a more diverse and inclusive global economic order